The Influence of Instructional Models on Badminton Skills Performance base on Motor Educability Levels - Gempar Al Hadist; Arif Fajar Prasetiyo (Universitas Pendidikan Indonesia, 2022)
This study aimed to investigate the effect of cooperative and conventional instructional models on badminton skills performance based on motor educability levels. The research method used in this study is an experimental method using a 2 X 2 factorial design. The population in this study was 270 junior high school students of 9 classes. The samples used were two classes with a total of 60 people. The sampling technique used is cluster random sampling. The instrument used is Badminton Skills Performance. The statistical analysis technique used is the two-way analysis of variance (ANAVA) at a significance level of 0.05. This study concludes that the instructional models significantly influence the performance of badminton skills; this study also shows no interaction between the instructional models and motor educability. The Teachers suggest using both instructional models for games activities characteristics to help achieve learning indicators.